Originally Posted by

**ajj86** g'(theta)=4-sec^2(theta)

So, you set the right side equal to zero:

4 - sec^2(theta) = 0

Using a little algebra:

sec^2(theta) = 4

Take the square root of both sides to get:

sec(theta) = 2

Now remember, sec(theta) = 1/cos(theta)

So, 1/cos(theta) = 2

Take the inverse of both sides to get:

cos(theta) = 1/2

I'm sure you know how to do the rest. I hope this helps.

Also, for the first problem, do some review of the chain rule. It will help you understand how to get the derivatives a lot better.